New Insights in Oral Health and Diets - Varzakas, Theodoros; Antoniadou, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The world of adult education needs information on instruments that provide behavioral changes and support the physical, emotional, and spiritual health of modern individuals. Under this scope, this Special Issue incorporates articles about modern perspectives on diet and coaching approaches that lead to new dietary habits.